A comparative investigation on the accuracy of Neosono Ultima EZ instrument, radiography and anexperimental apex locator in root canal working length measurement - Zarabian M; Nekoofar M.H; Marashi MS (Tehran University of Medical Sciences, 2004)
Various methods have already been suggested to measure the working length in root"ncanal therapy among which the use of paper point, tactile sense, radiography and electronic apex finder"ninstruments can be named. Investigations on EAL (Electronic Apex Locator) indicate that these instruments"ncan reduce the number of required radiography to a great extent. Moreover, in special cases such as patients"nwith high risk reflex, pregnant women, the mental disabled and handicapped and also in cases with special"nanatomical structures these instruments are proper substitutes for radiography."nPurpose: The aim of this study was to compare the accuracy of an Iranian made apex finder instrument with"nNeosono Ultima EZ and radiography."nMaterials and Methods: This study was conducted on 51 mandibular molars, devoid of calcification, internal"nand external resorption, severe root curve or fracture, which were extracted due to periodontal disease or"nsevere caries. All the specimens were washed in 2.5% hypochlorite sodium and washing with water, kept in"n10% formalin solution, under room temperature."nResults: The accuracy of the Iranian instrument was measured (81.8%) similar to that of radiography"n(81.2%). But the accuracy of Neosono Wtima EZ was (92.9%) which was higher than the two other methods."nConclusion: No statistically significant difference was found between Neosono Ultima EZ instrument and"ntwo other groups, using SPSS 10 statistical soft ware.